2020
DOI: 10.15294/komunitas.v12i1.20167
|View full text |Cite
|
Sign up to set email alerts
|

The Government Communication Mechanism in Reducing Violence Diffusion of Street Vendors Relocation Policy

Abstract: This research used descriptive qualitative method. Furthermore, this study aimed to identify actors, media, models, and the nature of message design in the relocation of street vendors, so that the so that conflicts in policy communication can be reduced. Informant of this research was government apparatus of Yogyakarta. The result of the research showed that Yogyakarta government as a system in communicating the street vendors’ relocation policy involves actors who play a collaborative and integrative role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Information seeking is a result of pressure or coercion of certain parties and is called coercive communication. Thus, information seeking, attitude changes and compliance can be influenced by persuasive communication (Al-Marshoudi et al, 2021;Perloff, 2003;Singhal & Kim, 2021) and coercive communication (Mani, 2017).…”
Section: Coercive Communication and Information Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…Information seeking is a result of pressure or coercion of certain parties and is called coercive communication. Thus, information seeking, attitude changes and compliance can be influenced by persuasive communication (Al-Marshoudi et al, 2021;Perloff, 2003;Singhal & Kim, 2021) and coercive communication (Mani, 2017).…”
Section: Coercive Communication and Information Seekingmentioning
confidence: 99%
“…Several previous studies have explained the effectiveness of coercive communication in changing the audience's behaviour. Several studies investigated public policy communication and have found that coercive communication affects public compliance (Mani, 2017;Sjostrom, 2006). Meanwhile, research conducted examined the problems of alcohol control in Switzerland and has discovered that coercive instruments are not related to the problems of alcohol control (Sager, 2009).…”
Section: Coercive Communication and Information Seekingmentioning
confidence: 99%